# Part III: The Power Stuff: Advanced Techniques in Java Maker Quick Response Code in Java Part III: The Power Stuff: Advanced Techniques

Part III: The Power Stuff: Advanced Techniques
QR Code JIS X 0510 Maker In Java
Using Barcode creation for Java Control to generate, create Denso QR Bar Code image in Java applications.
To summarize, you have the following: a2 = a4 = a6 = -a0 2! a0 4! -a0 6!
Generate Barcode In Java
Using Barcode creator for Java Control to generate, create barcode image in Java applications.
So now you can relate the even coefficients in general If n = 2m (in which m stands for a positive integer or zero): a n = a 2m =
Decoding Bar Code In Java
^ -1h a 0 ^ 2mh !
Painting Quick Response Code In C#.NET
Using Barcode generator for VS .NET Control to generate, create QR Code JIS X 0510 image in VS .NET applications.
m = 0, 1, 2, 3
Printing QR Code JIS X 0510 In .NET
Using Barcode generation for .NET Control to generate, create QR Code ISO/IEC18004 image in .NET applications.
Because you set a0 based on the initial conditions for a given problem, you can now find the even coefficients of the solution
Denso QR Bar Code Generator In VB.NET
Using Barcode generation for VS .NET Control to generate, create QR Code JIS X 0510 image in .NET framework applications.
Using the recurrence relation to find odd coefficients
Encoding Bar Code In Java
Using Barcode maker for Java Control to generate, create bar code image in Java applications.
Now you can move on to the odd coefficients Turn back to the recurrence relation in the previous section for the solution: (n + 2)(n + 1)an+2 + an = 0 You can see that for n = 1 you get: (3)(2)a3 + a1 = 0 So: a3 = - a1 ^ 3 h^ 2h
Generate ECC200 In Java
Using Barcode printer for Java Control to generate, create Data Matrix image in Java applications.
Taking a clue from the even coefficients in the previous section, you can see that (3)(2) = 3!, so you get this: a3 = - a1 3!
Barcode Generation In Java
Using Barcode encoder for Java Control to generate, create bar code image in Java applications.
Now, for n = 3 in the recurrence relation, you get: (5)(4)a5 + a3 = 0 or: a5 = -a3 ^ 5 h^ 4 h
UPC - 13 Drawer In Java
Using Barcode creator for Java Control to generate, create UPC - 13 image in Java applications.
9: Getting Serious with Power Series and Ordinary Points
Code 39 Maker In Java
Using Barcode encoder for Java Control to generate, create Code39 image in Java applications.
Substituting a3 in terms of a1 into this equation gives you: a5 = or: a5 = a1 5! a1 ^ 5 h^ 4 h^ 3!h
International Standard Serial Number Generation In Java
Using Barcode printer for Java Control to generate, create ISSN - 13 image in Java applications.
Substituting n = 5 into the recurrence relation gives you: (7)(6)a7 + a5 = 0 or: a7 = -a5 ^7 h^ 6 h
Recognizing GS1 - 13 In .NET Framework
Using Barcode scanner for .NET framework Control to read, scan read, scan image in .NET applications.
And substituting a5 into this equation gives you: a7 = - a1 ^7 h^ 6 h^ 5!h
Code-39 Scanner In .NET Framework
Using Barcode recognizer for .NET Control to read, scan read, scan image in .NET framework applications.
which means that: a7 = - a1 7!
Make Data Matrix 2d Barcode In .NET Framework
Using Barcode generator for .NET Control to generate, create DataMatrix image in VS .NET applications.
To sum up, the odd coefficients you have so far are: a3 = a5 = a7 = - a1 3! a1 5! - a1 7!
Using Barcode recognizer for .NET framework Control to read, scan read, scan image in .NET framework applications.
So now you can relate the odd coefficients of the solution this way in general, if n = 2m + 1: a n = a 2m + 1 =
Drawing Code 128A In .NET
Using Barcode creator for Visual Studio .NET Control to generate, create ANSI/AIM Code 128 image in .NET applications.
^ -1h a 1 ^ 2m + 1h !
Barcode Drawer In VS .NET
Using Barcode encoder for .NET framework Control to generate, create bar code image in .NET applications.
m = 0, 1, 2, 3
Making EAN13 In Visual Studio .NET
Using Barcode printer for .NET framework Control to generate, create European Article Number 13 image in .NET applications.
Putting together the solution
Code 128 Recognizer In .NET
Using Barcode scanner for .NET framework Control to read, scan read, scan image in .NET framework applications.
Using the two equations for even and odd coefficients from the previous sections, you get the following general solution to your differential equation in series terms:
Part III: The Power Stuff: Advanced Techniques
y = a0
^ -1h x 2m ^ 2mh !
+ a1
^ -1h x 2m + 1 ^ 2m + 1h !
That s the solution to the differential equation in series terms In this case, the two series are recognizable as cos(x) and sin(x) Here s sin(x):
^ -1h x 2n + 1 = sin x ^ 2n + 1h !
And here s cos x:
^ -1h x 2n = cos x ^ 2nh !
So you can rewrite the solution as: y = a0 cos(x) + a1 sin(x) The terms a0 and a1 are arbitrary constants (just like c0 and c1), and they re set by matching the initial conditions
When you don t know the solution beforehand
How do you use a power series to solve a differential equation for which you don t already know the solution For instance, what if you have an equation like this: d2y dy -x + 2y = 0 dx dx 2 Give it a try, using a power series like this: y=
The following sections will guide you through the process
Differentiating and substituting power series into the differential equation
Differentiating the power series from the previous section gives you the following equation: y l= ! na n x n - 1
n =1 3
9: Getting Serious with Power Series and Ordinary Points
And differentiating this gives you: y'' = ! n^ n - 1h a n x n - 2
3 n=2
Now for the fun part: substitution! Substituting these equations into the original differential equation gives you this result:
! n^ n - 1h a
3 n=2 3 n =1 3
x n-2
- x ! na n x n - 1 +2 !an x n = 0
Using the recurrence relation to find coefficients
Now it s time to equate powers of x on the left side of the equation to 0 on the right side Combining the coefficients for powers of x gives you this equation: [2a2 + 2a0] + [6a3 + a1] x + 12a4 x 2 + [20a5 a3] x 3 + [(n + 2)(n + 1) an+2 (n 2)an ] x n = 0 Note that every power of x must be 0 for the equation to work, so the last term in the previous equation gives you the recurrence relation for this solution: (n + 2)(n + 1) an+2 (n 2)an = 0 After some simplifying, you get: an+2 =